2016
DOI: 10.1007/s10753-016-0408-1
|View full text |Cite
|
Sign up to set email alerts
|

Polystyrene-Divinylbenzene-Based Adsorbents Reduce Endothelial Activation and Monocyte Adhesion Under Septic Conditions in a Pore Size-Dependent Manner

Abstract: Endothelial activation with excessive recruitment and adhesion of immune cells plays a central role in the progression of sepsis. We established a microfluidic system to study the activation of human umbilical vein endothelial cells by conditioned medium containing plasma from lipopolysaccharide-stimulated whole blood or from septic blood and to investigate the effect of adsorption of inflammatory mediators on endothelial activation. Treatment of stimulated whole blood with polystyrene-divinylbenzene-based cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…In addition to IL-6 removal and reduced vasopressor need, the third interesting finding of our study is the improvement in lung function. There is clear data from the field of experimental research, that hemoadsorption might also have a positive effect via protection of the vascular barrier function, 28 endothelial activation, and monocyte adhesion 29 as well as a limitation in endothelial damage, 30 resulting in less extravasation and better ventilation-perfusion matching. We observed improvements in oxygenation and also in lung mechanics during the course of hemoadsorption.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to IL-6 removal and reduced vasopressor need, the third interesting finding of our study is the improvement in lung function. There is clear data from the field of experimental research, that hemoadsorption might also have a positive effect via protection of the vascular barrier function, 28 endothelial activation, and monocyte adhesion 29 as well as a limitation in endothelial damage, 30 resulting in less extravasation and better ventilation-perfusion matching. We observed improvements in oxygenation and also in lung mechanics during the course of hemoadsorption.…”
Section: Discussionmentioning
confidence: 99%
“…It can block the interaction of monocytes with activated endothelial cells by impeding the binding of the monocytic integrin LFA-1 to endothelial ICAM-1 [ 61 ]. Accordingly, we have previously shown that septic plasma samples containing high ESM-1 levels failed to induce monocytic cell adhesion to endothelial cells in vitro [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This enhanced clearance however did not result in persistently reduced cytokine levels, presumably due to a dynamic release of cytokines over the course of treatment [ 21 ]. We further found that plasma samples from individual patients differed considerably with regard to their potential to induce endothelial activation in a cell culture model [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatment of lipopolysaccharide-stimulated whole blood with PS-DVB-based adsorbents attenuated subsequent endothelial activation almost to baseline levels and resulted in strongly reduced monocyte adhesion. In contrast to the reproducible endothelial activation observed with conditioned medium from lipopolysaccharide-stimulated whole blood, however, conditioned medium containing plasma from sepsis patients showed highly variable potential to induce endothelial activation despite comparable levels of pro-inflammatory cytokines (77), underscoring the inhomogeneity of sepsis patients and implying that cytokines that are most commonly used in experimental models of inflammation or sepsis may not be the main triggers of endothelial activation (78).…”
Section: Septic Plasma Shows Variable Potential To Trigger Endotheliamentioning
confidence: 98%
“…Various stimuli have been used to activate the endothelium in these experimental models, such as lipopolysaccharide, single cytokines, or cytokine mixtures. To reflect the complexity of a septic environment, we have previously used conditioned medium obtained by spiking cell culture medium with plasma from lipopolysaccharide-stimulated whole blood to induce HUVEC activation in a static as well as in a microfluidic model with defined shear conditions (7477), as shown in Figure 1. Treatment of lipopolysaccharide-stimulated whole blood with PS-DVB-based adsorbents attenuated subsequent endothelial activation almost to baseline levels and resulted in strongly reduced monocyte adhesion.…”
Section: Septic Plasma Shows Variable Potential To Trigger Endotheliamentioning
confidence: 99%